Investigating the Role of Verbal Working Memory in Young Children's Sentence Comprehension. Issue 2 (10th March 2013) - Boyle, Whitney; Lindell, Annukka K.; Kidd, Evan
Abstract : This study considers the role of verbal working memory in sentence comprehension in typically developing English‐speaking children. Fifty‐six ( N = 56) children aged 4;0–6;6 completed a test of language comprehension that contained sentences which varied in complexity, standardized tests of vocabulary and nonverbal intelligence, and three tests of memory that measured the three verbal components of Baddeley's model of Working Memory (WM): the phonological loop, the episodic buffer, and the central executive. The results showed that children experienced most difficulty comprehending sentences that contained noncanonical word order (passives and object relative clauses). A series of linear mixed effects models were run to analyze the contribution of each component of WM to sentence comprehension. In contrast to most previous studies, the measure of the central executive did not predict comprehension accuracy. A canonicity by episodic buffer interaction showed that the episodic buffer measure was positively associated with better performance on the noncanonical sentences. The results are discussed with reference to capacity‐limit and experience‐dependent approaches to language comprehension.